Changes in Hematological Parameters of Common Carp (Cyprinus carpio) Fi gerlings Fed on Pomegranate (Punica granatum) Peel Supplement - Sayed-Lafi, Raad M.; Sultan, Fatima A.M.; Al-Tameemi, Riyadh A. (Al-Mukhtar Journal of Sciences, 2023)
The present study aimed to determine the effect on different blood parameters (WBCs, RBC, HGB, HCT, MCV, MCH, and MCHC) in fingerlings of common carp (Cyprinus carpio) weighing 13.5 ± 1 g with pomegranate peels (Punica granatum) in their different forms, raw (PPR), alcoholic (PPA) and water (PPW), which were added to their feed as 0.5% and 1% respectively, in addition to the control treatment (21 replicates). A commercial diet was used containing 35% crude protein, 6% lipid, 12% Ash and 50 TVN for ten weeks. At the end of the experiment, blood was drawn from the heart of the fish, and analyses were performed. The results showed that RBCs, HGB and HCT improved significantly (P< 0.05), while there were no significant differences (P> 0.05) in WBCs, MCH, and MCHC. In short, we recommend adding pomegranate peels or extracts (alcoholic or aqueous) to common carp food at a rate not exceeding 1%.